The Influence Of Determinants Abuse of Addictive Substances (Drugs) and Mental Health in Adolescent - Astuti, Andriani Mei; Probowati, Rovica; Prakoso, Adi Buyu (Global Health Science Group, 2024)
Drugs are a complex problem in Indonesia, this is proven by the significant increase in the number of drug abusers or addicts. One of the factors causing the increase in drug consumption among teenagers is their attitude of ignoring applicable values, norms and laws. This study aims to determine the factors that dominate the occurrence of drug abuse in adolescents. The design of this research is descriptive correlative with a cross sectional approach. Sampling of 30 teenagers from total sampling statical metode. Data analysis used the Spearman Rho statistical test and binary logistic regression. The results showed that there was a relationship between age (p value = 0.005; OR = 33,925), peer influence (p value = 0.039; OR: 14,390). The most dominant factor in the occurrence of drug abuse in adolescents is age. Recommendations that can be conveyed from the results of research on children entering the adolescent transition phase should receive special assistance in their growth and development by creating emotional relationships and a sense of empathy for adolescence.